Implementasi Web Service pada Sistem Host-To-Host Pembayaran Biaya Akademik - Rohmat Gunawan; Alam Rahmatulloh (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2018)
The implementation of the online education fee payment system is one of the efforts to improve the quality of academic services. The process of paying academic fees by involving banks has facilitated financial data processing for higher education institutions. But because academic payment data is stored in the banking system, the payment data information cannot be automatically recorded in academic information systems managed by higher education institutions. The lack of recognition of academic information systems managed by tertiary education with information systems on the payment of academic fees managed by banks, has caused disruption to the smooth running of the academic process. Students who have made payments through a bank must submit proof of payment to the academic department at the higher education institution, to manually input data on the academic information system. This activity takes time and is repeated every payment period. In order to overcome these problems, system integration is done using web service technology. The experimental results from the research have built 3 main services (apiDataTumpul, apiUpdate, apiReversal), which are implemented on a host-to-host system architecture. Web service implementation can integrate both systems, so that data updates between systems can be done in real time.